The effect of dryer and trehalose concentration on characteristics of mangosteen as natural dyes - Taufik, Yusman; Widiantara, Tantan; Hariadi, Hari; Febryarto, Rony (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of this study was to determine the effect of the type of dryer and the addition of trehalose concentration on the physicochemical characteristics of mangosteen skin dye. The research design used a Randomized Group Design (RAK) with a 3x3 factorial pattern consisting of 2 (two) factors with 2 (two) replications, resulting in 18 experimental units. Factor d is the type of drying equipment consisting of 3 levels, namely d1 (freeze dryer), d2 (cabinet dryer), and d3 (rotary vacuum dryer), while factor t is the concentration of trehalose consisting of 3 levels, namely t1 (5%), t2 (10%), and t3 (15%). The responses in this study include chemical responses such as water content and pH value, and physical responses including color intensity, yield calculation, hygroscopicity, solubility, and aW. There are chemical and physical responses with selected samples, namely anthocyanin content, antioxidant activity, and Scanning Electron Microscope analysis. The results showed that the type of tool influences the water content, pH value, L*a*b* color intensity, total yield, solubility, and aW. The concentration of trehalose affects the water content, pH value, color intensity L*a*, yield amount, solubility, and aW, but does not affect the color intensity b*. The interaction between the type of drying equipment and trehalose concentration affects the pH value, color intensity a*b*, yield amount, solubility, and aW, but does not affect the water content response and color intensity L*.